Respuesta :
Answer:
(x+4)^2 + (y+2)^2 = 5
Explanation:
Using the midpoint formula, we find that the center of the circle is (-4, -2). We also calculate using the distance formula that between the two points is [tex]\sqrt{2\\0}[/tex]or [tex]2\sqrt{5\\\\}[/tex].
Because we found the diameter, to find the radius we divide by two, getting [tex]\sqrt{5\\\\}[/tex].
Now that we have the center, (-4, -2), and the distance from the center to the radius, we can put the information into the circle equation:
(x-h)^2 + (y-k)^2 = r^2
This becomes:
(x+4)^2 + (y+2)^2 = 5
Answer:
-4 , -2 , 5
Step-by-step explanation:
(x-(-4))^2+(y-(-2))^2=5
since 2 negatives equal a positive, - -4 = +4
same thing for -2
(x+4)^2+(y+2)^2=5